Asian hedge funds risk and return dynamics and diversification benefits before and after the global financial crisis - Naeem, Zain (2012)
This research looks at the performance of the Asian region hedge funds based on risk and return measures and then sees the effect of the Global Financial Crisis of 2007. In addition to that, it maps the risk and return profiles on a linear regression model based on the strategies used by the hedge funds and sees the effects on the models due to the crisis. Lastly, it looks into the diversification benefits provided by the hedge funds. In accordance with all these three test criteria, the researcher has seen that the best strategy before the crisis was the distressed debt and the best strategy after the crisis was managed futures. The researcher has also concluded that there are benefits to investing in hedge funds, however, the strategy risk should be understood with the returns. Taking an active approach and using flexibility, a hedge fund manager in the Asian region, can derive excess return by keeping a close eye on the market conditions and responding accordingly.